Andrographolide Prevents EV-D68 Replication by Inhibiting the Acidification of Virus-Containing Endocytic Vesicles - Wang, Dongyin; Guo, Haoran; Chang, Junliang; Wang, Dong; Liu, Bin; Gao, Pujun; Wei, Wei (Frontiers in Microbiology, 2018)
Enterovirus D68 (EV-D68) has emerged as a significant respiratory pathogen that can cause severe respiratory disease and acute neurologic disease. At present, there are no approved antiviral agents or vaccines for EV-D68. In this study, we demonstrate that andrographolide (ADO), an active component of Andrographis paniculata, exerts substantial antiviral activity against EV-D68 infection. ADO treatment dramatically inhibited EV-D68 RNA replication (EC50 = 3.45 µM) and protein synthesis without producing significant cytotoxicity at virucidal concentrations. ADO-treated cells did not show any changes in host immune activation, EV-D68 attachment, or viral 5′ UTR activity. Using a pH-sensitive fluorescent indicator system for endocytosis in living cells, we found that ADO prevented the acidification of endocytic vesicles after receptor-mediated endocytosis. Finally, we showed that ADO inhibited the viral replication of circulating isolated EV-D68 strains. In summary, our results demonstrate that ADO suppresses EV-D68 replication by targeting the maturation of virus-containing endosomes of EV-D68. This mechanism represents a promising strategy for drug development.